T-Cell-Based Immunotherapy for Osteosarcoma: Challenges and Opportunities - Wang, Zhan; Li, Binghao; Ren, Yingqing; Ye, Zhaoming (Frontiers in Immunology, 2016)
Abstract Even though combining surgery with chemotherapy has significantly improved the prognosis of osteosarcoma patients, advanced, metastatic or recurrent osteosarcomas are often nonresponsive to chemotherapy, making development of novel efficient therapeutic methods an urgent need. Adoptive immunotherapy has the potential to be a useful non-surgical modality for treatment of osteosarcoma. Recently, alternative strategies, including immunotherapies using naturally occurring or genetically modified T cells, have been found to hold promise in the treatment of hematologic malignancies and solid tumors. In this review, we will discuss possible T-cell-based therapies against osteosarcoma with a special emphasis on combination strategies to improve the effectiveness of ATCT (adoptive T cell transfer), and thus to provide a rationale for the clinical development of immunotherapies.